2023
DOI: 10.1002/wcs.1643
|View full text |Cite
|
Sign up to set email alerts
|

Understanding preferences in infancy

Abstract: A preference is defined as a dispositional state that helps explain why a person chooses one option over another. Preference understanding is a significant part of interpreting and predicting others' behavior, which can also help to guide social encounters, for instance, to initiate interactions and even form relationships based on shared preferences. Cognitive developmental research in the past several decades has revealed that infants have relatively sophisticated understandings about others' preferences, as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 133 publications
0
1
0
Order By: Relevance
“…We build upon a body of experiments that have found that infants and toddlers show an early capacity for social evaluation: They preferentially look to and reach for agents who help others over agents who hinder others in the pursuit of their goals (Choi & Luo, 2023 ; Hamlin & Wynn, 2011 ; Hamlin et al, 2007 , 2010 ; Hamlin, Ullman, et al, 2013 ; Margoni & Surian, 2018 ; Schlingloff et al, 2020 ; Woo et al, 2022 ). Although there have been failures to replicate these findings (Salvadori et al, 2015 ; Schlingloff et al, 2020 ), a meta-analysis of experiments probing early social evaluations has found that infants and toddlers demonstrate a significant preference for helpers over hinderers (Margoni & Surian, 2018 ).…”
Section: Introductionmentioning
confidence: 99%
“…We build upon a body of experiments that have found that infants and toddlers show an early capacity for social evaluation: They preferentially look to and reach for agents who help others over agents who hinder others in the pursuit of their goals (Choi & Luo, 2023 ; Hamlin & Wynn, 2011 ; Hamlin et al, 2007 , 2010 ; Hamlin, Ullman, et al, 2013 ; Margoni & Surian, 2018 ; Schlingloff et al, 2020 ; Woo et al, 2022 ). Although there have been failures to replicate these findings (Salvadori et al, 2015 ; Schlingloff et al, 2020 ), a meta-analysis of experiments probing early social evaluations has found that infants and toddlers demonstrate a significant preference for helpers over hinderers (Margoni & Surian, 2018 ).…”
Section: Introductionmentioning
confidence: 99%